(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores the role of interactive multimedia tools (IMTs) in fostering self-regulated learning (SRL) among university students. Drawing on theories of motivation and cognitive engagement, the research highlights how IMTs, such as video lectures, quizzes, and gamified activities, enhance students’ autonomy, engagement, and metacognitive strategies. While IMTs effectively promote motivation and active learning, findings suggest they have limitations in fostering deeper self-regulation skills like planning and reflection. The study recommends integrating IMTs with additional instructional scaffolding to maximize their potential and enhance higher education SRL outcomes.